Israel Vs. Iran : The Shadow War - Katz, Yaakov, 1979- (Book collections on Project MUSE., 2012)
"The shadow war between Israel and Iran has been raging for more than three decades, ever since the Iranian revolution of 1979 ushered in a fundamentalist regime whose sworn enemies have consistently included, first and foremost, Israel and the United States. Israel, especially, has borne the brunt of attacks from Iran's two most powerful proxies--Hamas in the Gaza Strip and Hezbollah in Lebanon. Iran's nuclear ambitions raise the stakes immeasurably. Israel vs. Iran evaluates the threat to Israel's security posed by a nuclear Iran, including competing perceptions of the threat, and analyzes Israel's military and diplomatic options. Drawing on in-depth research and invaluable access to the Israeli defense establishment, including interviews with key decision makers, Israeli military correspondent Yaakov Katz and Israeli military historian Yoaz Hendel describe behind-the-scenes Israeli strategic military deliberations and intelligence analysis since the Second Lebanon War of 2006. The authors focus on pivotal military events in this shadow war with Iran, including the Syrian reactor bombing and Operation Cast Lead in the Gaza Strip, as well as assassinations of key Hezbollah operatives, Iranian nuclear scientists, and Syrian officials. Assassinations, computer viruses, and Western sanctions might not be enough to stop Iran, the authors argue. They outline the choice Israel faces: launch a military strike, which could lead to an all-out regional war, or tacitly accept a nuclear Iran, which would lead to a new balance of power in the Middle East. In 2012 Israel appears closer than ever to making a decision."